Second generation antipsychotics in 'real-life' paediatric patients. Adverse drug reactions and clinical outcomes of drug switch. (1st December 2016) - Rafaniello, Concetta; Pozzi, Marco; Pisano, Simone; Ferrajolo, Carmen; Bertella, Silvana; Sportiello, Liberata; Carnovale, Carla; Sullo, Maria Giuseppa; Cattaneo, Dario; Gentili, Marta; Rizzo, Renata; Pascotto, Antonio; et al.
ABSTRACT: Objective : Gap in knowledge on benefit/risk ratio of second generation antipsychotics (SGA) in the paediatric population represents a challenge for the scientific community. This study aims to analyse all suspected adverse drug reactions (ADRs) to SGA observed during the study period; compare the safety profiles of risperidone and aripiprazole; evaluate the effect of switching from risperidone to aripiprazole or to a first generation antipsychotic (FGA). Methods : Prospective analysis of spontaneously reported ADRs concerning 184 paediatric outpatients between 2012 and 2014.; clinical outcomes of drug switch were evaluated. Results : Out of the 184 patients, 130 experienced at least one ADR; ADRs were usually not serious and more frequently associated with aripiprazole. Switching to aripiprazole was associated with better results than switching to FGAs in the Clinical Global Impression scale- Efficacy (CGI-E) scores (p = 0.018), Disturbed behaviour checklist-parents (DBC-P) self-absorption subscale (p = 0.010); only a trend for difference between changing to aripiprazole vs FGAs in the DBC-P total score (p = 0.054) and social relating subscale (p = 0.053) was observed. Conclusions : SGAs safety data were consistent with the ones already known; however, there is still a need to improve the knowledge in pharmacovigilance field among clinicians. Switching to aripiprazole may be a valid alternative to risperidone.